An evolving paradigm of agricultural mechanization development: How much can Africa learn from Asia? - Diao, Xinshen; Takeshima, Hiroyuki; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
Agricultural mechanization in Africa south of the Sahara — especially for small farms and businesses — requires a new paradigm to meet the needs of the continent’s evolving farming systems. Can Asia, with its recent success in adopting mechanization, offer a model for Africa? An Evolving Paradigm of Agricultural Mechanization Development analyzes the experiences of eight Asian and five African countries. The authors explore crucial government roles in boosting and supporting mechanization, from import policies to promotion policies to public good policies. Potential approaches presented to facilitating mechanization in Africa include prioritizing market-led hiring services, eliminating distortions, and developing appropriate technologies for the African context. The role of agricultural mechanization within overall agricultural and rural transformation strategies in Africa is also discussed. The book’s recommendations and insights should be useful to national policymakers and the development community, who can adapt this knowledge to local contexts and use it as a foundation for further research.